2010
DOI: 10.1007/s13539-010-0008-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a high‐caloric protein‐rich oral nutritional supplement in patients with chronic heart failure and cachexia on quality of life, body composition, and inflammation markers: a randomized, double‐blind pilot study

Abstract: The prevalence of cardiac cachexia in chronic heart failure is approximately 5% to 15% and 18-month mortality rates can reach 50%. Treatment with angiotensin-converting enzyme inhibitors and beta-blockers may confer some benefit but no proven therapy exists. We tested the effects of an oral nutritional supplement in cachectic patients with heart failure. This was a prospective, randomized, double-blind, placebo-controlled pilot study which randomized 29 patients to a high-caloric (600 kcal) high-protein (20 g)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
165
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 147 publications
(174 citation statements)
references
References 35 publications
3
165
1
5
Order By: Relevance
“…It has been shown that malnutrition and low protein intake can be responsible for muscle wasting in heart failure patients, particularly in those with sedentary life style and physical inactivity 26, 27, 28, 29. Although the albumin and protein level were within the normal limits in our study population, it cannot be easily concluded that the protein turnover is not disturbed in our study population.…”
Section: Discussioncontrasting
confidence: 55%
“…It has been shown that malnutrition and low protein intake can be responsible for muscle wasting in heart failure patients, particularly in those with sedentary life style and physical inactivity 26, 27, 28, 29. Although the albumin and protein level were within the normal limits in our study population, it cannot be easily concluded that the protein turnover is not disturbed in our study population.…”
Section: Discussioncontrasting
confidence: 55%
“…A pilot randomized trial of 29 patients with severe HF and non-edema weight loss >7.5 % found that 20 g of protein supplementation per day had beneficial effects on body composition and Minnesota Living With Heart Failure Questionnaire scores [24]. The gradual age-related decline in muscle mass and strength known as sarcopenia should be differentiated from cardiac cachexia, as the latter is characterized by rapid loss of skeletal muscle mass and adipose tissue driven by inflammatory cytokines and typically resistant to nutritional interventions [25].…”
Section: Therapeutic Implications Of Frailty In Hf: General Principlesmentioning
confidence: 99%
“…Nutritional studies have been a cornerstone of therapeutic research in cachexia and sarcopenia. Rozentryt et al performed a clinical trial of nutritional intervention in cardiac cachexia [94]. A diet containing 600 kcal per day for 6 weeks (with relatively high fat content to reduce volume) increased weight during the treatment and the subsequent 12-week follow-up period (70% fat tissue, 30% muscle tissue) and had anti-inflammatory effects (reduction of TNF levels).…”
Section: Search Strategymentioning
confidence: 99%